Responsibility as a Primary Environmental Virtue in Islam - Le Duc, Anthony (PT FORMOSA CENDEKIA GLOBAL, 2023)
The exploration of environmental virtues within religious teachings has gained significant attention in recent years, as scholars in the field of religious environmentalism seek to apply the framework of environmental virtue ethics to religious contexts. This paper focuses on Islam and proposes that responsibility is a fundamental environmental virtue within this tradition. By employing a qualitative analysis method, the paper examines scriptural and scholarly resources within Islam to provide a comprehensive understanding of this virtue. The argument posits that responsibility is considered an environmental virtue due to its essential role in guiding Muslims' attitudes and behaviors towards God, themselves, society, and the natural world. It emphasizes that the concept of responsibility in Islam can only be fully comprehended within the broader Islamic worldview, which acknowledges God as the ultimate source and owner of all things and recognizes the pivotal role of human beings in God's divine plan. This research not only contributes to the broader discourse on religious environmental virtue ethics but also specifically advances the development of an Islamic environmental virtue ethics framework.